2022
DOI: 10.1002/marc.202100933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of External Magnetic Field on Bulk Heterojunction Polymer Solar Cells

Abstract: Polymer solar cells (PSCs) with a bulk heterojunction (BHJ) device structure have incredible advantages, such as low‐cost fabrication and flexibility. However, the power conversion efficiency (PCE) of BHJ PSCs needs to be further improved to realize their practical applications. In this study, boosted PCEs from PSCs based on BHJ composites incorporated with Fe3O4 magnetic nanoparticles (MNPs), aligned by an external magnetic field (EMF), are reported. It is found that the coercive electric field within the Fe3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Besides chemical methodologies, there are also some other attempts of using physical methods—such as magnetic fields, electric fields, and alternating electromagnetic fields—to control the morphology of the active layer ( 22 , 23 ). However, the experimental attempts to implement such physical methods have not been exceptionally successful and the best efficiency achieved was only about 11% using these methods ( 24 , 25 ). The reasons for these unsuccessful attempts were not investigated in detail, but could be due to some of the following factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides chemical methodologies, there are also some other attempts of using physical methods—such as magnetic fields, electric fields, and alternating electromagnetic fields—to control the morphology of the active layer ( 22 , 23 ). However, the experimental attempts to implement such physical methods have not been exceptionally successful and the best efficiency achieved was only about 11% using these methods ( 24 , 25 ). The reasons for these unsuccessful attempts were not investigated in detail, but could be due to some of the following factors.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, it would be difficult to significantly change the nanostructure of the solid films as the molecules have limited mobility in the solid state ( 22 , 26 ). In another study, the authors had to introduce inorganic magnetic particles into the BHJ blends, possibly leading to negative effects on the morphology and charge separation process within the active layers ( 25 ). Although these initial attempts of using physical methodologies were not highly successful, it is still worthwhile to further investigate physical approaches, as they may offer morphological effects that cannot be achieved using conventional chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study indicated that an increase in magnetic field strength resulted in higher shunt, series, and short-circuited current values across all levels of doping. Few more studies have also described the possible impact of magnetic fields on the performance degradation of PV panels (Combari et al, 2017;Sourabié et al, 2017;Ndeto et al, 2020;Panmuang and Photong, 2021;Wu et al, 2023). Previous studies investigated the effect of constant magnetic field to measure the minority charge carrier mobilization in hetero-junction bipolar transistor.…”
Section: Introductionmentioning
confidence: 99%